Larvas de Scinax rizibilis (Bokermann) (Anura, Hylidae): avaliando o efeito parental - Bastos, Rogério P.; Haddad, Celio Fernando Baptista [UNESP] (Sociedade Brasileira de Zoologia, 2001)
A controlled experiment, related with the mating system of Scinax rizibilis (Bokermann, 1964), was conducted to assess if larval variation could be due to size of male or its ability to manage an amplexus. Adult individuals were caught during breeding activity (from February 1993 to January 1994), in a temporary pond in the municipality of Ribeirão Branco. São Paulo State, southeastern Brazil. The duration of the larval period was not different between tadpoles of large and small males, nor was it different between tadpoles coming from natural or artificial pairs. The reproductive status of the male (if it had managed an amplexus) also did not influence the total length nor the mass of the tadpoles close to metamorphosis. However, tadpoles of larger and heavier males were, on average, approximately 5.5% and 11% larger and heavier, respectively, than tadpoles of smaller males. These results indicate that the breeding system of S. rizibilis could potentially have a directional effect on the larval characteristics.
Tadpoles of Scinax rizibilis (Bokermann) (Anura, Hylidae): evaluating the paternal effects
Keywords: Scinax rizibilis; mating system; larval characteristic